Ethical Challenges of Virtual Reality Technology Interventions for the Vulnerabilities of Patients With Chronic Pain: Exploration of Technician Responsibility - Siyu Zhou; Diane Gromala; Leyu Wang (JMIR Publications, 2023)
Chronic pain, a common disease, is a crucial global public health concern. Approximately 20% of the worldwide population is affected by chronic pain, which accounts for 15% to 20% of hospital visits. In Canada, approximately 7.6 million people-or 1 in 5 people-experience chronic pain. Among this population, 60% has either lost their employment or experienced a reduction in income as a result of their pain. The proportion of older people (aged ≥65 years) with chronic pain is high, comprising one-third of the total older population. In addition, the causes of chronic pain and its cures are unknown, and treatment is limited by these unknowns and the dangers of opioids. These essential factors make patients with chronic pain one of the most vulnerable populations. The use of emerging virtual reality (VR) technology as an intervention for chronic pain has consistently demonstrated early effectiveness and has been termed as a "nonpharmacological analgesic." Nevertheless, we must remain vigilant about the potential ethical risks of VR interventions, as inappropriate VR interventions may exacerbate the vulnerabilities of patients. Currently, a central challenge for VR developers is the ambiguity of patient vulnerability and the unpredictability of ethical dilemmas. Therefore, our paper focused on the vulnerability and ethical dilemmas faced by patients with chronic pain in VR interventions. Through an experience-based, prospective ethical examination, we have identified both existing and potential new vulnerabilities and specific manifestations that patients with chronic pain may encounter in VR interventions. Our aim was to highlight the ethical risks that may be present in VR interventions. On one hand, this can help raise awareness among technology developers regarding the vulnerabilities of patients with chronic pain and mitigate technological ethical risks. In addition, it can assist technology developers in determining the priorities for VR technology interventions. These efforts collectively lay a solid foundation for the comprehensive realization of responsible VR technology interventions.